2016
DOI: 10.29173/slw6911
|View full text |Cite
|
Sign up to set email alerts
|

From Teacher to School Librarian Leader and Instructional Partner: A Proposed Transformation Framework for Educators of Preservice School Librarians

Abstract: This paper presents a framework for educators to prepare preservice school librarians to become transformational leaders and instructional partners. With leadership as its central focus, this conceptual framework includes the constructs of Tools, Training, Teams, Time, Targets, and Trust. These constructs are described in relation to school librarian leadership, principal leadership, and the context within which transformation takes place. The Six Ts model can be used in all school librarian preparation progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Roles are also defined in relationship to the other roles an organization comprises (Ebbers & Wijnberg, 2017). School librarians have a specialized set of performance responsibilities in their schools, that differ from the responsibilities they may have experienced in their work as classroom teachers (Baker, 2016). Roles may change in response to organizational or environmental pressures, and/or as the employee assigned to the role performs it, changing the organization's perception of the role (Ebbers & Wijnberg, 2017;Yun, Takeuchi, & Liu, 2007).…”
Section: Roles and School Librariansmentioning
confidence: 99%
“…Roles are also defined in relationship to the other roles an organization comprises (Ebbers & Wijnberg, 2017). School librarians have a specialized set of performance responsibilities in their schools, that differ from the responsibilities they may have experienced in their work as classroom teachers (Baker, 2016). Roles may change in response to organizational or environmental pressures, and/or as the employee assigned to the role performs it, changing the organization's perception of the role (Ebbers & Wijnberg, 2017;Yun, Takeuchi, & Liu, 2007).…”
Section: Roles and School Librariansmentioning
confidence: 99%
“…A teacher librarian need to be a leader to develop a school library programme, ensure visibility in the school, and show the wider school community the importance of the library to the school by building awareness in the school community of the teacher librarian's role and the benefits of the school library. Baker (2016) mentioned that accomplished school librarians are leaders in their profession, in the administration of their libraries, instructional leaders who provide learning opportunities for teachers and students and technology integration leaders.…”
Section: Leadershipmentioning
confidence: 99%
“…Authors such as Baker (2016), Clephane (2014), Church (2011) and Johnston (2012a) have identified the need for teacher librarians worldwide to assume more leadership roles in this technological era. To assume the position of technology leaders in schools, it is imperative that the teacher librarian works closely with both classroom teachers and students to integrate technology in the teaching-learning process and teach information literacy.…”
Section: Leadershipmentioning
confidence: 99%
See 2 more Smart Citations